2013
DOI: 10.1007/s11906-013-0331-x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and Potassium and the Pathogenesis of Hypertension

Abstract: The evidence relating blood pressure to salt intake in humans originates from population studies and randomized clinical trials of interventions on dietary salt intake. Estimates from meta-analyses of trials in normotensive subjects generally are similar to estimates derived from prospective population studies (+1.7-mm Hg increase in systolic blood pressure per 100 mmol increment in 24-hour urinary sodium). This estimate, however, does not translate into an increased risk of incident hypertension in subjects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Diet manipulation studies such as dietary approaches to stop hypertension (DASH) suggest that adoption of a healthy diet (rich in fruits and vegetables) could lower high blood pressure [ 18 , 19 ]. Similarly, compounds like dietary sodium (present in table salt) and dietary potassium also have a great impact on blood pressure and associated vascular diseases [ 20 , 21 , 22 ]. Moreover, various clinical studies have demonstrated that macronutrients (protein, fat, and carbohydrate) can play key role in the management of high blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Diet manipulation studies such as dietary approaches to stop hypertension (DASH) suggest that adoption of a healthy diet (rich in fruits and vegetables) could lower high blood pressure [ 18 , 19 ]. Similarly, compounds like dietary sodium (present in table salt) and dietary potassium also have a great impact on blood pressure and associated vascular diseases [ 20 , 21 , 22 ]. Moreover, various clinical studies have demonstrated that macronutrients (protein, fat, and carbohydrate) can play key role in the management of high blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, individuals receive nutrient minerals mainly from dietary foods. Drinking water containing high levels of calcium, magnesium, and potassium can be crucial in the prevention of magnesium deficiency 5,32 as well as contribute significantly to the daily calcium and potassium intake for persons with calcium or potassium-deficient diets 10,[33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and magnesium benefit health in preventing several diseases including cardiovascular diseases [5][6][7] . Sodium is found considerably in daily foods and because of its undesired hypertensinogenic effect, its presence in drinking water is considered a health risk [8][9][10] . Iron in drinking water results in disagreeable taste and rusty colour 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A question thus arises as to whether the significant association observed in southern Chinese can be extrapolated to northern Chinese, considering the fact that China has a vast territory with obvious regional differentiation in socio-economic development levels and the physical environmental conditions, which can result in different causal factors of disease [24]. For example, it is widely known that high-salt diet can induce or aggravate hypertension in both animal models and humans [25], [26]. However, salt consumption between northern and southern Chinese differs remarkably.…”
Section: Discussionmentioning
confidence: 99%